Combined Application of Osteoplastic Material in the Bone Defects Treatment (Eurasian Medical Research Periodical, 2022)
The aim of the article is to stimulate the healing of bone defects in the jaws, applying a combined osteoplastic preparation. 72 patients with retained teeth were treated by using combined osteoplastic material. The result of the study is a significant reduction in the number of local complications after bone grafting applying combined osteoplastic drugs